The Influence of Electronic Word of Mouth and Social Media Marketing On The Purchasing Decision of Small and Medium Enterprises (Case Study On Diyos Shoes Cleaning In Medan City) - Roy Mulyadi Mardiyos; Arlina Nurbaity Lubis; Parapat Gultom (PT. Publikasiku Academic Solution, 2024)
This research aims to determine and analyze the influence of electronic word of mouth and social media marketing on purchasing decisions for small and medium enterprises (case study on Diyos Shoes Cleaning). This research is associative research and the type of data used is quantitative data. The population in this research is the unknown number of Diyos Shoes Cleaning customers in Medan City. The number of samples in this research was 170 customers. The sampling technique uses purposive sampling with the criteria of being 17 years of age and over, having social media, following the Diyos Shoes Cleaning social media account and domiciled in Medan City. The data analysis used is Multiple Linear Regression Analysis. The results of this research show that simultaneously electronic word of mouth and social media marketing have a significant influence on purchasing decisions for Diyos Shoes Cleaning services. Partially, electronic word of mouth and social media marketing have a positive and significant effect on purchasing decisions for Diyos Shoes Cleaning services.